PERKEMBANGAN EKSPANSI BISNIS PT. TELEKOMUNIKASI INDONESIA INTERNASIONAL (TELIN) DI SINGAPURA PADA TAHUN 2018 – 2020 - Febriana Ayonda; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
PT Telekomunikasi Indonesia Internasional (Telin) is a multinational company engaged in technology, information and communication in Indonesia. Telin made its first expansion in Singapore. Singapore is a country that is close to Indonesia and has a strategic position as a place for companies to develop business in the telecommunications industry. The main focus of the international business owned by PT Telin Singapore is the data center or data center. The data center is one of the main facilities for a company that is able to help store and provide company information as well as other information which of course can benefit the company and the country of origin of the company. This study uses the perspective of Liberalism with the level of group analysis, the theory used in this study is the theory of OLI (Ownership, Location, Internalization) by John H. Dunning. The qualitative method in this study uses secondary data obtained from the company's official website, books, journals, articles, and websites. This study shows that the presence of MNC expansion has an impact on the country, both the host country and the home country. The expansion carried out by PT Telekomunikasi Indonesia Internasional(Telin) in Singapore adds to the cooperative relationship between Indonesia and Singapore. The international business developed by PT Telin from 2018-2020 in Singapore has grown from a data center business to a submarine cable system that can connect many countries, showing that PT Telin is able to compete in Singapore in the telecommunications sector. Keywords: Data Center, Expansion, Telecommunications, Telin Singapore, Perspective of Liberalism, Theory of OLI